2018
DOI: 10.1507/endocrj.ej17-0380
|View full text |Cite
|
Sign up to set email alerts
|

Proposed cut-off value of CA19-9 for detecting pancreatic cancer in patients with diabetes: a case-control study

Abstract: Pancreatic cancer is a highly lethal malignancy. CA19-9 is a well-known marker for diagnosis of pancreatic cancer, but the serum CA19-9 level is reported to be elevated in patients with poorly controlled diabetes. This study evaluated the sensitivity, specificity, and cut-off value of serum CA19-9 for detection of pancreatic cancer in patients with diabetes. A case-control study of 236 patients was performed. The case group was selected from diabetic patients with pancreatic cancer, while one control was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…After treatment of hyperglycemic state, the serum CA 19-9 levels of diabetic patients were more than 57.14 U/ml, in which the presence of malignancy diseases should be suspected and evaluated. Recently, Mariko, Murakami, et al proposed that 75 U/ml serum CA 19-9 should be used as the cutoff value in screening pancreatic cancer in patients with diabetes because the sensitivity and specificity of serum CA 19-9 are 69.5 % and 98.2 % [19], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment of hyperglycemic state, the serum CA 19-9 levels of diabetic patients were more than 57.14 U/ml, in which the presence of malignancy diseases should be suspected and evaluated. Recently, Mariko, Murakami, et al proposed that 75 U/ml serum CA 19-9 should be used as the cutoff value in screening pancreatic cancer in patients with diabetes because the sensitivity and specificity of serum CA 19-9 are 69.5 % and 98.2 % [19], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…42 A cut-off of 75 U/ml showed a sensitivity and specificity of 69.5% and 98.2% for the detection of PC, respectively, but mostly in advanced stages. 5 It has moreover been reported that w5% of the population are Lewis blood group-negative [Le (a-b-)] and cannot synthesize CA19-9: these individuals may show false negative levels of CA19-9. 43 Circulating tumor DNA.…”
Section: Biological Tests and Predictive Models To Detect Pc In People With Diabetesmentioning
confidence: 99%
“…PC prognosis is extremely poor (overall survival <10% at 5 years): this is largely due to the difficulties in identifying PC at an early stage as well as its aggressive behaviour (local invasion, distant metastases, and poor response to therapy). 4 , 5 The development of strategies for early diagnosis of resectable PC is therefore critical for improved survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al [ 17 ] have measured CA 19-9 levels before and after PC surgery and neoadjuvant chemotherapy, proving that its levels before treatment can predict outcome, since failure to normalize was correlated with poor prognosis for this category of patients. However, another team of researchers point out that CA 19-9 levels can be elevated in diabetic patients, therefore proposing a cut-off of 75 U/mL for separating diabetics from pancreatic cancer patients [ 18 ]. This is important to keep in mind when evaluating this marker’s levels, especially as long as diabetes is a common disease.…”
Section: Carbon Nanotubesmentioning
confidence: 99%